2011
DOI: 10.1088/0143-0807/32/4/018
|View full text |Cite
|
Sign up to set email alerts
|

The photoelectric effect: experimental confirmation concerning a widespread misconception in the theory

Abstract: The photoelectric effect is widely taught in schools and institutions. It is common knowledge that in order for photoelectrons to be emitted, the energy of the incoming photons must be greater than the work function of the irradiated metal (i.e. hν > ϕemitter). However, what may not be as commonly known is that the ‘ϕ’ in Einstein's photoelectric equation (eVs = hν − ϕ) is often implicitly and mistakenly taken as the work function of the emitter (or anode) rather than that of the collector (or cathode). This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…In recent years, researchers have focused their attentions to the students' understanding of quantum physics concepts at different school levels (Asikainen & Hirvonen, 2009;De Leone & Oberem, 2004;McKagan, Handley, Perkins, & Wieman, 2009;Steinberg, Oberem, & McDermott, 1996;Yıldız & Büyükkasap, 2011). Photoelectric effect is one of the important quantum physics topics that play a crucial role in understanding the photon model of light (McKagan et al, 2009;Wong et al, 2011). Unfortunately, the previous researches reported that most of the students from different educational levels have serious learning difficulties in understanding the basic aspects of photoelectric effect such as interpreting experimental set-up, predicting experimental results and its' relation to the photon model of light (De Leone & Oberem, 2004;McKagan et al, 2009;Sokolowski, 2013;Steinberg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have focused their attentions to the students' understanding of quantum physics concepts at different school levels (Asikainen & Hirvonen, 2009;De Leone & Oberem, 2004;McKagan, Handley, Perkins, & Wieman, 2009;Steinberg, Oberem, & McDermott, 1996;Yıldız & Büyükkasap, 2011). Photoelectric effect is one of the important quantum physics topics that play a crucial role in understanding the photon model of light (McKagan et al, 2009;Wong et al, 2011). Unfortunately, the previous researches reported that most of the students from different educational levels have serious learning difficulties in understanding the basic aspects of photoelectric effect such as interpreting experimental set-up, predicting experimental results and its' relation to the photon model of light (De Leone & Oberem, 2004;McKagan et al, 2009;Sokolowski, 2013;Steinberg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the cathode and anode plates are generally made of different materials, the work function f cannot simply be used in the equation, as the work functions of both the two metals must be considered [32,33]. That is, the formula can be satisfied only when the cathode and anode plates are made of the same material.…”
Section: Further Considerations To Explain Real Experimental Datamentioning
confidence: 99%
“…Figure 4 shows the I-V characteristics according to the type of metals used for cathode and anode [33]. Zinc and Nickel were chosen as the emitter and collector of electrons, and three different cases are Zn-Zn (h ).…”
Section: Further Considerations To Explain Real Experimental Datamentioning
confidence: 99%
“…The photoelectric effect is representative of the finding that shining light on certain materials can eject electrons from that material (Wong et al, ). The minimum amount of energy necessary to eject electrons from a particular material is referred to as the work function.…”
Section: The Photoelectric Effect and Improving Public Healthmentioning
confidence: 99%